EFEKTIVITAS METODE ROLE PLAY TERHADAP KEMAMPUAN INTERKULTURAL DALAM BAHASA INGGRIS KELAS V SDN DI KOTA CIREBON - Khodijah, Nur; Wahyuni, Dewi; Sholeh, Abdul (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2025)
The intercultural competence of fifth-grade elementary school students in Cirebon City is still low. This low ability is evident in the students’ lack of courage to express their opinions, limited vocabulary, and minimal understanding of the cultural context underlying the language. One creative and innovative learning method that can be applied is using the role-playing method to create an effective learning environment. This study aims to describe the application of the role-play method to intercultural competence in English for 5th-grade elementary school students in Cirebon City and to determine the effectiveness of the role-play method on intercultural competence in English for 5th-grade elementary school students in Cirebon City. This type of research is quantitative research using an experimental research method with a One Group Pretest-Posttest Design. The total population is all fifth-grade students at SDN Kebon Melati 1, Cirebon City, and the sample consists of 22 students. The research instruments used are tests and observation sheets. The research results indicate the implementation and effectiveness of the role-play method on intercultural competence in English for fifth-grade elementary school students in Cirebon City. This is based on the results of the N-Gain test, which showed that the mean increase in intercultural competence after the treatment was 0.7542, meaning that since g > 0.7, the N-Gain value was categorized as high. It can be seen from the significant value (2-tailed) < 0.05, indicating effectiveness, and there is a Sig value of 0.001, meaning that since 0.001 < 0.05, it can be concluded that there is a significant effectiveness of the role-playing method on intercultural competence in English for 5th-grade students at Cirebon City Elementary Schools).